Precision medicine: a master stroke - Singh, Alok (International Journal of Advances in Medicine, 2017)
Precision medicine is an idea of customization of health facilities as per the needs and demands of individual patient. Precise medicine leads to customized therapy to patients according to genetic profile because this provides information regarding susceptibility to disease and likelihood of response to treatment. It tends to use genetic information of a person to diagnose or treat their disease with sharing of this knowledge to establish a composite record which can be utilized in order to make available superior treatment to other patients also. Precision Medicine is going to be future of medicine. It collaborates technology, basic medical science and clinical records in order to throw lights on the aetio-pathogenesis of disease establish new target based therapy and eventually work for betterment of mankind.